2021
DOI: 10.1080/00207233.2021.1929469
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel nanocomposite based on date stones/CuFe2O4 nanoparticles for eliminating cationic and anionic dyes from aqueous solution

Abstract: In this study, the date stones/CuFe2O4 nanocomposite was synthesized by a graft of CuFe2O4 nanoparticles in the surface of date stones (DS) for the removal of rhodamine B (RhB) and methyl orange (MO) from aqueous solutions. The adsorption of RhB and MO on DS@CuFe2O4 shows good agreement with second-order kinetic and Langmuir isotherm models. The maximum adsorption capacity was found to be 555.56 03 mg g -1 and 303.03 mg g -1 for RhB and MO, respectively.This adsorption is spontaneous and endothermic. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…This decrease was attributed to the occupation of available sites on the BC@MgO NPs surface (El Messaoudi et al, 2021d). These results indicated that the BC@MgO NPs is a durable material for regeneration studies.…”
Section: Regeneration and Reusabilitymentioning
confidence: 76%
“…This decrease was attributed to the occupation of available sites on the BC@MgO NPs surface (El Messaoudi et al, 2021d). These results indicated that the BC@MgO NPs is a durable material for regeneration studies.…”
Section: Regeneration and Reusabilitymentioning
confidence: 76%
“…The separated photogenerated holes in the valence band (h VB + ) on the SnO 2 will oxidize MB dye molecules directly due to their strong oxidizing ability ( eqn (8) ). 33 h VB + + MB → MB + ˙ …”
Section: Resultsmentioning
confidence: 99%
“…This separation of the electronhole pairs can be improved by transition metal gra or composite to form heterojunction or complex formation. [26][27][28][29][30][31][32][33] Mostly, p-n type heterojunction of composites materials were reported to have effective photogenerated electrons/holes separation due to electric eld created in the junction in virtue to enhance the photocatalytic activity. [34][35][36] Few example for the p-type CFO utilized to decorated the diverse metal oxides and applicable to the various research eld in recent universe; TiO 2 /CFO, 37,38 work was reported for n-SnO 2 /p-CFO; it was used for sensing, optical, and enhancing the electrical properties of the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Dyestuffs also impede the penetration of sunlight, which is compulsory for photosynthesis in the aquatic environment, thus hampering the natural growth of ora and fauna. 29 A number of processes/techniques are applied to get rid of hazardous textile effluent (dyes) such as electro-peroxone, 30 precipitation, membrane ltration, otation, adsorption, coagulation, electro-coagulation, ion exchange, 31 photocatalysis, irradiation, 32 haloalkaliphilic bacterial consortium, 33 electro-coagulation and electro-Fenton, 34 Fenton and photo-Fenton processes, 35 biocatalytic treatment, 36 etc. All the processes described here have inherent advantages and disadvantages and are chosen based on feasibility study.…”
Section: Introductionmentioning
confidence: 99%